The role of self-determination theory in developing curriculum for flipped classroom learning: A Case Study of First-Year Business Undergraduate Course - Narendran, Roshni; Almeida, Shamika; Coombes, Rebecca; Hardie, Geraldine; Quintana-Smark, Eunice; Zaher, Nabi; Wang, Hui-Ling; Chowdhury, Ahabab; Stevenson, Barry (Journal of University Teaching and Learning Practice, 2018)
This study examines the influence of adopting a student-centered active learning approach based on self-determination theory (SDT) to develop independent and motivated first-year Australian business undergraduates. Existing literature demonstrates how active learningapproaches can help to improve student motivation. However, there are no empirical studies to assess the influence of active learningclassroom activities on student academic performance during their first year of tertiary studies. The aim of our study is to contribute to knowledge by integrating self-determination theory, and ‘at-home ethnographic’ research approach to reflect on how active learning-classroom strategies can help tertiary business students become independent learners and improve their academic performance. The active learning-classroom approach included a scaffolded assessment structure; timely and ongoing tutor feedback on assessment criteria and learning outcomes of the scaffolded assessments; and social/peer-based learning activities within and outside of the classroom to support student performance. The authors draw on an ‘at-home ethnographic’ research approach, which allowed the teaching team to use their observations during the 13 weeks of teaching, and team reflections, to describe not only what they witnessed, but also their experiences of how students interacted, and what they did within the classroom environment. The study shows that students became autonomous and positively benefited from the scaffolded assessment structure while evolving to become competent, independent learners due to the continuous feedback they received on their assessments, and to the active peer learning within and outside of the classroom. Moreover, the group assessments provided a platform to engage with academic literature, which, in turn, helped students to challenge their understanding of the concepts by engaging in critical analysis with their peers. The findings can help future tertiary learning designers to develop first year assessments that will support students to become independent learners and reduce the level of attrition during the first year of tertiary education.